Germline C1GALT1C1 mutation causes a multisystem chaperonopathy - Erger, Florian; Aryal, Rajindra P.; Reusch, Björn; Matsumoto, Yasuyuki; Meyer, Robert; Zeng, Junwei; Knopp, Cordula; Noel, Maxence; Muerner, Lukas; Wenzel, Andrea; Kohl, Stefan; Tschernoster, Nikolai; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Mutations in genes encoding molecular chaperones can lead to chaperonopathies, but none have so far been identified causing congenital disorders of glycosylation. Here we identified two maternal half-brothers with a novel chaperonopathy, causing impaired protein O-glycosylation. The patients have a decreased activity of T-synthase (C1GALT1), an enzyme that exclusively synthesizes the T-antigen, a ubiquitous O-glycan core structure and precursor for all extended O-glycans. The T-synthase function is dependent on its specific molecular chaperone Cosmc, which is encoded by X-chromosomal C1GALT1C1. Both patients carry the hemizygous variant c.59C>A (p.Ala20Asp; A20D-Cosmc) in C1GALT1C1. They exhibit developmental delay, immunodeficiency, short stature, thrombocytopenia, and acute kidney injury (AKI) resembling atypical hemolytic uremic syndrome. Their heterozygous mother and maternal grandmother show an attenuated phenotype with skewed X-inactivation in blood. AKI in the male patients proved fully responsive to treatment with the complement inhibitor Eculizumab. This germline variant occurs within the transmembrane domain of Cosmc, resulting in dramatically reduced expression of the Cosmc protein. Although A20D-Cosmc is functional, its decreased expression, though in a cell or tissue-specific manner, causes a large reduction of T-synthase protein and activity, which accordingly leads to expression of varied amounts of pathological Tn-antigen (GalNAcα1-O-Ser/Thr/Tyr) on multiple glycoproteins. Transient transfection of patient lymphoblastoid cells with wild-type C1GALT1C1 partially rescued the T-synthase and glycosylation defect. Interestingly, all four affected individuals have high levels of galactose-deficient IgA1 in sera. These results demonstrate that the A20D-Cosmc mutation defines a novel O-glycan chaperonopathy and causes the altered O-glycosylation status in these patients.
Online veröffentlicht: 22. Mai 2023
Gesehen am 11.10.2023